2004
DOI: 10.1159/000079829
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Genome Sequence of <i> Bacillus licheniformis </i>DSM13, an Organism with Great Industrial Potential

Abstract: The genome of Bacillus licheniformis DSM13 consists of a single chromosome that has a size of 4,222,748 base pairs. The average G+C ratio is 46.2%. 4,286 open reading frames, 72 tRNA genes, 7 rRNA operons and 20 transposase genes were identified. The genome shows a marked co-linearity with Bacillus subtilis but contains defined inserted regions that can be identified at the sequence as well as at the functional level. B. licheniformis DSM13 has a well-conserved secretory system, no polyketide biosynthesis, but… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
235
0
17

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(260 citation statements)
references
References 86 publications
5
235
0
17
Order By: Relevance
“…The circular chromosome (3,918,589 bp) is somewhat smaller than that of the closely related B. subtilis 9 and Bacillus licheniformis 10,11 , primarily owing to the absence of prophage islands, which are abundant in the B. subtilis 168 genome. Deletions, altogether spanning 495 kb, were detected in regions equivalent to B. subtilis prophages 1 to 7, the phage SPbC2 and the skin element (Supplementary Table 1 online).…”
Section: General Genomic Features and Dna Islandsmentioning
confidence: 99%
“…The circular chromosome (3,918,589 bp) is somewhat smaller than that of the closely related B. subtilis 9 and Bacillus licheniformis 10,11 , primarily owing to the absence of prophage islands, which are abundant in the B. subtilis 168 genome. Deletions, altogether spanning 495 kb, were detected in regions equivalent to B. subtilis prophages 1 to 7, the phage SPbC2 and the skin element (Supplementary Table 1 online).…”
Section: General Genomic Features and Dna Islandsmentioning
confidence: 99%
“…The industrial applications of microorganisms include the food industry, pharmaceutical industry, metallurgy, mining, oil, leather, light chemical industry, and other industries [94][95][96][97]. Through a genomic study of Bacillus subtilis, a series of genes related to the production of antibiotics and important industrial enzymes was identified [98]. Lactobacillus is an important microecological regulator that has been used in the food fermentation process; genomics research of this organism will help researchers identify the key functional genes and then transform the strain to make it more suitable for industrial production processes [99].…”
Section: Microbiotamentioning
confidence: 99%
“…The B. licheniformis belongs to the B. subtilis group (group II) of the genus Bacillus together with other well-known species whose complete genome sequence has been determined. 23 The genome of B. licheniformis ATCC 14580 is in the form of a circular chromosome of 4,222,336 base-pairs (bp), which was predicted to be consist of 4,208 protein-coding sequences (CDSs). Based on a broad investigation on B. licheniformis genome, at least 82 of the 4,208 genes are likely to encode secreted proteins and enzymes.…”
Section: Identification Of Putative Bacillus Sp Sl-1 Enzymesmentioning
confidence: 99%
“…The B. licheniformis is an important producer of exoenzymes and has been used for decades in large-scale manufacturing the industrial and pharmaceutical enzymes such as different proteases, α-amylase, penicillinase, pentosanase, β-mannanase and several pectinolytic enzymes. 22,23 Based on complete genome sequence of B. licheniformis, many new genes for enzymes with potential biotechnological and pharmaceutical applications were found. 23 With the recent advances in biotechnology, various enzymes have been identified and designed or purposely engineered to produce more (and most likely new) chemicals and materials from cheaper (and renewable) resources, which will consequently contribute to establishing a bio-based economy.…”
mentioning
confidence: 99%
See 1 more Smart Citation